Change of Terminology? Change of Law? An Overall Assessment of the Provisions of the Civil Code of Québec Relating to Prior Claims and Hypothecs - Macdonald, Roderick (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1992)
The provisions of the Civil Code of Québec dealing with Prior Claims and Hypothecs constitute an ambitious, although only partly successful, reform of the law relating to security devices. Given the policy objectives underlying any regime of security on property, three major problems with the new Code are immediately apparent: the failure to rationalize the scheme of non-consensual priorities and legal hypothecs; the failure to provide explicitly for an imperative regime of registration and realisation recourses governing any legal transaction which in substance functions as security on property; and the failure to redefine the concept of hypothec to account for its extension to universalities, and incorporeal property. Nevertheless, ordinary canons of codal interpretation give the judiciary sufficient resources to correct, by principled reference to the basic policy goals of this area of the law, most of the textual deficiencies in Book Six of the Civil Code of Québec.